Training on the Preparation of Cinnamon and Honey Infusions to Reduce Menstrual Pain among Adolescent Girls - Riris Sitorus; ⁠Mayang Citra Hariati; Diah Evawanna Anuhgera; Grace Erlyn D. Sitohang; Desideria Yosepha Ginting (JURNAL PENGMAS KESTRA (JPK), 2026)
Menstrual pain is one of the most common reproductive health problems experienced by adolescent girls and may adversely affect learning concentration, productivity, and overall quality of life. Limited knowledge regarding non-pharmacological approaches to menstrual pain management often leads adolescents to endure the discomfort or rely on analgesic medications without adequate information. This community service program aimed to enhance adolescent girls’ knowledge and practical skills in preparing cinnamon and honey infusions as a complementary approach to alleviating menstrual pain. The program was implemented using an educational and participatory approach through health education sessions, interactive discussions, demonstrations, and hands-on practice. A total of 25 adolescent girls who had experienced menstruation participated in the activity. Program evaluation was conducted using pretests and posttests to assess knowledge improvement, observational checklists to evaluate practical skills, and participant satisfaction questionnaires. The results demonstrated a substantial increase in participants’ mean knowledge score, from 58.13 before the training to 87.73 after the intervention. The highest improvement (64.96%) was observed in knowledge related to the preparation procedure of cinnamon and honey infusions. Skills assessment revealed that 60.0% of participants achieved a very good category and 32.0% achieved a good category in preparing the infusion. Participant satisfaction was also remarkably high, with 84.0% reporting that they were very satisfied with the program. These findings indicate that training on the preparation of cinnamon and honey infusions is effective in improving adolescent girls’ knowledge and skills regarding non-pharmacological menstrual pain management through the utilization of safe, affordable, and readily available natural ingredients.